Tropospheric forcing of the 2019 Antarctic sudden stratospheric warming - Shen, X; Wang, L; Osprey, S (American Geophysical Union, 2020)
The strongest and most persistent upward propagation of zonal wavenumber 1 (WN1) Rossby waves from the troposphere on record led to the rare Antarctic sudden stratospheric warming (SSW) in September 2019. The dynamical contribution from instantaneous anomalous WN1 and its linear interference with the climatological WN1 contributed equally to the event. The unprecedented WN1 planetary wave behavior is further attributed to a long‐lived midlatitude circumpolar Rossby wave train in the troposphere that was sustained by anomalous convection, first over the subtropical Pacific Ocean east of Australia and then over the eastern South Pacific. Besides the tropospheric wave forcing, the phase of the quasi‐biennial oscillation in the upper stratosphere also facilitated the weakening of polar vortex. Moreover, this SSW strongly influenced the tropospheric circulation via the Southern annular mode, favoring conditions linked to the 2019 bushfires in eastern Australia.